Peran perempuan dalam berwirausaha menuju pengembangan industri ekonomi kreatif di Desa Wisata Menari Getasan Kabupaten Semarang - Saadati, Nila (Journal of Economics Research and Policy Studies, 2022)
This research identifies the role of women as entrepreneurs. This study uses qualitative research methods carried out by field research. The location of this research is in Tanon "Dancing Tourism Village" Getasan, Kab. Semarang. The existence and development of the Tourism Village for approximately ten years has positively impacted the community by increasing residents' income because they can sell their plantation and livestock products. Besides that, they can also encourage the community to provide homestays. Business activities in the form of household creative industry activities are carried out by utilizing local raw materials found in the hamlet, with workers from their own families for the milk soap and hand chips industries. Professional conservation is the actual involvement of mothers because the dominant people are farmers and breeders. Thus, the husband's job is also the wife's job because the wife will always help her husband do his work daily to improve the family's standard of living.